Brief Critiques on Chain of Command, Unity of Command, Span of Control and Leadership in Health Sector of Nepal - Nayak, Shravan Kumar (Health Prospect, 2018)
DOI: http://dx.doi.org/10.3126/hprospect.v10i0.5644 Health Prospect Vol.10 2011, pp.27